2023
DOI: 10.1021/acs.est.3c02302
|View full text |Cite
|
Sign up to set email alerts
|

Redox Oscillations Activate Thermodynamically Stable Iron Minerals for Enhanced Reactive Oxygen Species Production

Abstract: Reactive oxygen species (ROS) play key roles in driving biogeochemical processes. Recent studies have revealed nonphotochemical electron transfer from redox-active substances (e.g., iron minerals) to oxygen as a new route for ROS production. Yet, naturally occurring iron minerals mainly exist in thermodynamically stable forms, restraining their potential for driving ROS production. Here, we report that tide-induced redox oscillations can activate thermodynamically stable iron minerals for enhanced ROS producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 55 publications
1
15
1
Order By: Relevance
“…The redox oscillations of chemically active minerals are intrinsically involved in various geochemical-biological cycles on Earth due to their crucial role in redox reactions. Particularly, the conversion of transition-metal ions, such as Fe­(II)/Fe­(III) and Mn­(III)/Mn­(IV), plays a pivotal role in other elemental cycles and organic matter turnover. , The past few decades have witnessed an unprecedented booming scene in the study of subsurface geochemical processes driven by iron-bearing minerals, focusing on pollutant transformation in both fundamental research and practical applications. , Among numerous iron-bearing minerals, the reduced Fe­(II) minerals are the most common and exhibit outstanding pollutant-transforming activity, partly due to their inherent surface reactivity. Mackinawite (FeS), a quintessential reduced Fe­(II) mineral, plays a fundamental role in the global Fe cycles and exhibits significant reactivity in biogeochemical processes. The pioneering work on using FeS for pollutant removal can be historically traced back to the 1990s . Since then, numerous studies have utilized FeS as an efficient reductant for the elimination of reducible organic compounds and heavy metals in natural anaerobic settings. , However, the oxygen-depleted settings often transition to oxygen-enriched environments due to various natural disturbances (e.g., groundwater fluctuations) and human interventions (e.g., remediation efforts). , Consequently, recent research on the transport, fate, and orientation of pollutants influenced by FeS in the presence of O 2 has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The redox oscillations of chemically active minerals are intrinsically involved in various geochemical-biological cycles on Earth due to their crucial role in redox reactions. Particularly, the conversion of transition-metal ions, such as Fe­(II)/Fe­(III) and Mn­(III)/Mn­(IV), plays a pivotal role in other elemental cycles and organic matter turnover. , The past few decades have witnessed an unprecedented booming scene in the study of subsurface geochemical processes driven by iron-bearing minerals, focusing on pollutant transformation in both fundamental research and practical applications. , Among numerous iron-bearing minerals, the reduced Fe­(II) minerals are the most common and exhibit outstanding pollutant-transforming activity, partly due to their inherent surface reactivity. Mackinawite (FeS), a quintessential reduced Fe­(II) mineral, plays a fundamental role in the global Fe cycles and exhibits significant reactivity in biogeochemical processes. The pioneering work on using FeS for pollutant removal can be historically traced back to the 1990s . Since then, numerous studies have utilized FeS as an efficient reductant for the elimination of reducible organic compounds and heavy metals in natural anaerobic settings. , However, the oxygen-depleted settings often transition to oxygen-enriched environments due to various natural disturbances (e.g., groundwater fluctuations) and human interventions (e.g., remediation efforts). , Consequently, recent research on the transport, fate, and orientation of pollutants influenced by FeS in the presence of O 2 has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…FIA-CL was applied for detecting • OH production from oxidation of reduced substances, a key source of • OH in soils (Figure a). , The potential adsorption of 5-OH-PHTH to soils was assessed. The adsorption of 5-OH-PHTH was <10% within 10 min and increased to over 90% after 2 h (Figure S13).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyl radical ( • OH) is a highly reactive species that plays a crucial role in a wide range of important chemical reactions in nature. , In the sunlit atmosphere and aquatic systems, • OH is generated via photochemical reactions such as ozone photolysis and photosensitization of organic matters. In natural waters, • OH drives rapid element cycles (e.g., oxidation and mineralization of organic carbon), as well as transformation of pollutants. In the atmosphere, • OH is responsible for the rapid conversion of gaseous pollutants, such as volatile organic compounds (VOCs) and nitrogen oxides (NO x ), into secondary organic aerosol (SOA) and nitrate. These chemical reactions are crucial in the formation and growth of fine particles during haze events. While photochemical reactions are the primary pathway for the generation of • OH in sunlit environments, recent studies have revealed that • OH can also be produced under dark conditions triggered by electron transfer from microbes and reduced geomaterials (e.g., reduced Fe and S minerals and organic matter) to O 2 . Therefore, • OH exists in nonsunlit regions, including soils and sediments, where it plays a role in biogeochemical processes and pollutant dynamics. To assess the role of • OH in those environmental processes, it is fundamental to develop • OH analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…During these periods, GRs are thought to have been abundant and likely shepherded marine geochemistry at the interface between land, air and sea [21,24,57]. Prior to the GOE and the subsequent proliferation of O 2 in marine environments, geochemically generated radical species [39,[58][59][60][61], thermochemical processes [22,62], natural electrochemical processes [63][64][65], photochemistry [23,61], nitrogen oxides [18,66] and nitrogen oxyanions [67,68], may have served as potential surrogates for the oxidation of GR and thus CH 4 , creating a CH 4 sink within the ancient Archean ocean. As O 2 concentrations increased following the GOE, the oxidation of GR-bearing oceans may have played a role in the drawdown of atmospheric CH 4 concentrations [10], impacting climate throughout the Proterozoic [69,70].…”
Section: Methane Oxidation On the Ancient Earthmentioning
confidence: 99%